Clinical Efficacy of Canrenone in Restoring Sinus Rhythm in Patients With Atrial Fibrillation—A Pilot, Randomized, Double-Blind Study - Rafał Dąbrowski MD, PhD; Agnieszka Segiet-Święcicka MD, PhD; Stefan Sawicki MD, PhD; Ilona Kowalik MD, PhD; Krzysztof Jaworski MD, PhD; Michał Farkowski MD, PhD; Agata Kubaszek-Kornatowska MD, PhD; Piotr Michałek MD, PhD; Mirosław Dłużniewski MD, PhD; Hanna Szwed MD, PhD; Tomasz Hryniewiecki MD, PhD; Jarosław Karwowski PhD (Journal of Cardiovascular Pharmacology and Therapeutics)
Background and aims Renin-angiotensin-aldosterone system (RAAS) inhibition is an upstream therapy for managing atrial fibrillation (AF). Of all RAAS-inhibiting agents, only canrenone in the form of potassium canrenoate, a specific inhibitor of mineralocorticoid receptors, is administered intravenously. We evaluated the clinical efficacy of intravenous potassium canrenoate in restoring sinus rhythm in patients with paroxysmal AF episodes. Methods This double-center, randomized, double-blind study comprised 52 patients with AF (lasting <48 h) in stable cardiopulmonary conditions who were eligible for cardioversion. The patients were randomly assigned to receive a slow intravenous bolus of 10 ml either as a placebo (0.9% saline) or canrenone (200 mg). The primary endpoint was the return of sinus rhythm within 2 h after drug administration. Results Of 52 patients, 27 (51.9%) and 25 (48.1%) were treated with placebo and canrenone, respectively. The median patient age was 68 years, and 27 patients (51.9%) were men. Sinus rhythm restoration during the follow-up period occurred in 3 (11.5%) and 4 (16.0%) patients in the placebo and canrenone arms ( P  = .477), respectively. Adverse events were observed in 2 (7.4%) and 0 (0.0%) patients in the placebo and canrenone arms, respectively ( P  = .170). Conclusions Intravenous canrenone is not effective in the sinus rhythm restoration among the patients with paroxysmal AF. ClinicalTrials.gov. NCT03536806